2014
DOI: 10.1590/0034-737x201461060014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biostimulant application on production and flavonoid content of marigold (Calendula officinalis L.)

Abstract: The production of medicinal plants as raw material for industry must associate quality with biomass formation and, with this purpose, the application of plant growth regulators has been studied in these crops. The objective of this study was to evaluate the effect of a biostimulant on growth, inflorescence production and flavonoid content in marigold. The experiment was conducted in a greenhouse and the treatments consisted of increasing doses of the biostimulant (0, 3, 6, 9, 12 and 15 mL L-1) applied by folia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…In addition, PBs' effects could be ascribed to the movability of plant growth regulators (PGRs) and the power to promote complex regulatory actions that interact among disparate biochemical reactions [127]. Some amino acids could influence growth through their connection to gibberellin biosynthesis [128]; PBs can modify a plant's hormonal status and employ authority over its growth.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In addition, PBs' effects could be ascribed to the movability of plant growth regulators (PGRs) and the power to promote complex regulatory actions that interact among disparate biochemical reactions [127]. Some amino acids could influence growth through their connection to gibberellin biosynthesis [128]; PBs can modify a plant's hormonal status and employ authority over its growth.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Application of biostimulants (undisclosed brand-name) containing GA (50 mg/L) and CK (90 mg/L) increased the number of leaves, flower heads and the total flavonoid content of marigold plants inflorescences [106]. Peppers (Capsicum annuum L.) treated with Megafol® (0.2% 40 mL; GA & CK content) had increased Ca uptake in Using Biostimulants Containing Phytohormones to Recover Hail-Damaged Essential Oil Plants DOI: http://dx.doi.org/10.5772/intechopen.102398 the foliage material and fruits.…”
Section: Natural Biostimulants-containing Phytohormones As a Recovery...mentioning
confidence: 99%
“…Biostimulants are defined as organically based plant-promoting substances/microorganisms applied to soil to increase the nutrient uptake, stimulate plant growth, increase tolerance to abiotic and biotic challenges, and improve product quality [39]. Several works with vegetable crops and medicinal crops showed that the use of biostimulants increases plant growth by increasing nutrient availability and thus nutrient plant content and antioxidant enzyme activity in the plants [39][40][41], and in the medicinal plants also increased the synthesis of the secondary compounds of medicinal interest [42].…”
Section: Agronomic Assessment Of the N Recovery Solutionmentioning
confidence: 99%